Growth and productivity response of Pakchong grass (Pennisetum purpureum cv. Thailand) to palm compost - Rani, Rani; Neli, Neli; Muchlis, Rita Zurina; Rita, Wismalinda; Suharnas, Edwar (Jurnal Ilmu Peternakan Terapan, 2026)
This study aims to evaluate the effect of palm frond compost fertilizer on the productivity of Pakchong grass (Pennisetum purpureum cv. Thailand) as livestock feed. The study was conducted at the UPTD-PPT IB Livestock and Animal Health Service of Bengkulu Province from July 2024 to April 2025 using a randomized block design (RBD) with four compost dose treatments (T0, T10, T20, and T30 tons/ha) and three replicates. The parameters observed included plant height, leaf width, stem circumference, and number of tillers. The results showed that compost application did not have a significant effect on the first harvest, but a significant increase was observed in the second harvest. The 30 tons/ha treatment produced the best growth, with plant height reaching 620.7 cm, stem circumference 57.42 mm, leaf width 10.77 cm, and an average of five tillers per clump. This indicates that oil palm frond compost has the potential to be an effective organic fertilizer in the long term, after the decomposition process has run optimally. Thus, the utilization of oil palm frond waste not only increases forage productivity but also supports sustainable agriculture through environmentally friendly waste management.